Pengembangan Pemasaran UMKM Bakmie Koh Aho Dengan Pemanfaatan Media Digital - Rimadias, Santi; Ardelia, Flora; Olivia, Gabrielle; Vernanda, Louisa (Abdimas Indonesian Journal, 2023)
This dedication aims to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the modern era, specifically focusing on the Aho noodle business. The main issues involve the underutilization of technology and a lack of digital marketing. This dedication proposes the application of information technology and digital marketing to expand market reach. The implementation methods include remapping and utilizing technology. The achieved results involve increased sales, technological understanding, and market expansion. The implementation of these strategies is expected to strengthen noodle MSMEs amid the increasingly digital and competitive business dynamics.